PENGEMBANGAN E-MODUL UNTUK PEMBELAJARAN ILMU PENGETAHUAN ALAM MATERI SISTEM PENCERNAAN MANUSIA DI MADRASAH TSANAWIYAH - Mutmainnah Mutmainnah; Aunurrahman Aunurrahman; Warneri Warneri (Universitas Tanjungpura, 2022)
AbstractThis study aims to produce an e-module for science learning materials for the human digestivesystem at MTS, find a profile of electronic modules for learning science for the humandigestive system at MTS, and determine learning outcomes using electronic modules forlearning science for materials for the human digestive system at MTS. The research methodused is a combination research and development method Borg and Gall and ADDIE. Theresearch population in this study were students of class VIIIA, VIIIB and VIIIC. The profileof the development of e-modules for learning science on human digestive system materials injunior high schools includes 3 main parts, namely introduction, content and evaluation. E-module development consists of several stages consisting of expert validation consisting ofmaterial experts, design experts and media experts. Individual trials with 3 students in grade8A, revision of test results, small group trials with 12 students, namely 6 students in each class8A and 8B, product revision, large group trials with 30 students, namely 15 students. ongrades 8A and 8B, respectively, and revision of the final product. The implementation wascarried out on 27 students of class VIIIC. The results showed that the development of theelectronic module developed in this assessment was considered valid in the range of values0-4 with an average value of 3.77 material expert validity, 3.93 design expert validity and3.54 media expert validity, which means that the electronic module can used. The electronicmodule profile includes an introduction section, a content section and an evaluation sectionKeywords: Electronic Module Development, Natural Science, Human Digestive System.